2022
DOI: 10.3390/s22197232
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Digital Twin Framework for an Industrial Robotic Drilling Process

Abstract: A digital twin is a digital representation of a physical entity that is updated in real-time by transfer of data between physical and digital (virtual) entities. In this manuscript we aim to introduce a digital twin framework for robotic drilling. Initially, a generic reference model is proposed to highlight elements of the digital twin relevant to robotic drilling. Then, a precise reference digital twin architecture model is developed, based on available standards and technologies. Finally, real-time visualis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…The most common classification is the general classification into physical space and cyber space (also called virtual or cloud space/layer) [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Some authors explicitly mention the communication between these two spaces [ 89 , 91 , 94 , 95 , 97 ]. Several authors present a more fine-grained classification of infrastructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common classification is the general classification into physical space and cyber space (also called virtual or cloud space/layer) [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Some authors explicitly mention the communication between these two spaces [ 89 , 91 , 94 , 95 , 97 ]. Several authors present a more fine-grained classification of infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…In order to be able to exchange data between the physical space and the cyber space, a corresponding network is necessary, which establishes a bidirectional connection between the physical and virtual aspects [ 87 , 88 , 90 , 92 , 95 , 97 , 101 , 108 , 109 ]. The communication takes place via interfaces that connect the physical space and the cyber space [ 89 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad Farhadi et al demonstrated a DT of a drilling robot sans graphical interface, still capable of monitoring and controlling machining parameters [18]. Advanced DT models often involve complex technologies like machine learning and artificial intelligence, indicating significant optimizations with various levels of implementation complexity [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, various communication pro-tocols can establish these connections, such as 5G uRRLC, OPC-UA, and MTConnect [19]. Ahmad Farhadi et al utilized OPC-UA as a universal model for facilitating machine-to-machine data exchange [18]. Therefore, a central contribution of this paper is the exploration of Node-RED as a centralized hub managing diverse communication protocols, striving to overcome standardization barriers through a tool capable of handling and integrating various protocols within a single control and monitoring framework.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation